2015
DOI: 10.1007/s00167-015-3544-5
|View full text |Cite
|
Sign up to set email alerts
|

Increasing incidence of acute Achilles tendon rupture and a noticeable decline in surgical treatment from 1994 to 2013. A nationwide registry study of 33,160 patients

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
281
2
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(317 citation statements)
references
References 23 publications
11
281
2
5
Order By: Relevance
“…The Achilles tendon is the strongest tendon in the human body and yet it is vulnerable to complete rupture, which most frequently occurs in men 30‐50 years of age that participate in recreational sports sporadically . The prevalence has been reported to be ~18 per 100 000 individuals per year with an incidence that appears to be on the rise .…”
Section: Introductionmentioning
confidence: 99%
“…The Achilles tendon is the strongest tendon in the human body and yet it is vulnerable to complete rupture, which most frequently occurs in men 30‐50 years of age that participate in recreational sports sporadically . The prevalence has been reported to be ~18 per 100 000 individuals per year with an incidence that appears to be on the rise .…”
Section: Introductionmentioning
confidence: 99%
“…An increasing incidence has also been reported in Finland and Sweden . However, the proportion of operatively treated patients has recently declined …”
Section: Introductionmentioning
confidence: 99%
“…The number of Achilles tendon (AT) ruptures has been increasing in last two decades. [1][2][3][4] A recent large epidemiological study demonstrated that the annual incidence of AT rupture has increased in Canada from 18.0 to 29.3 per 10 5 in a 10-year period. 1 An increasing incidence has also been reported in Finland 2 and Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…It usually happens in patients between 30 and 40 years old [21] and significantly more men than women [22]. The incidence rate has trended higher [23, 24] recently. Rupture is located in the middle distance at the tendon insertion 2–6 cm [25].…”
Section: Discussionmentioning
confidence: 99%